2023
DOI: 10.1038/s41598-023-28599-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cardiovascular disease risk and hearing loss in a clinical population

Abstract: Hearing loss has been associated with individual cardiovascular disease (CVD) risk factors and, to a lesser extent, CVD risk metrics. However, these relationships are understudied in clinical populations. We conducted a retrospective study of electronic health records to evaluate the relationship between hearing loss and CVD risk burden. Hearing loss was defined as puretone average (PTA0.5,1,2,4) > 20 dB hearing level (HL). Optimal CVD risk was defined as nondiabetic, nonsmoking, systolic blood pressure (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Kurtosis has shown a strong correlation in studies assessing its association with cardiovascular disease risk. Some studies have indicated that different calculation time windows for kurtosis may influence its correlation with noise-induced health damage [19][20] , and the adjustment coefficient of kurtosis may also impact health risk assessment results [16] . Thus, the effects of calculation time windows and adjustment coefficients for kurtosis on the assessment of noise-induced health risks warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurtosis has shown a strong correlation in studies assessing its association with cardiovascular disease risk. Some studies have indicated that different calculation time windows for kurtosis may influence its correlation with noise-induced health damage [19][20] , and the adjustment coefficient of kurtosis may also impact health risk assessment results [16] . Thus, the effects of calculation time windows and adjustment coefficients for kurtosis on the assessment of noise-induced health risks warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has unveiled an association between cardiovascular disease risk and hearing loss in clinical populations, with factors like diabetes, hypertension, and smoking being the primary influencing factors in males [20] . Therefore, when studying the relationship between noise and cardiovascular disease risk, considering hearing loss as an intermediary factor may yield promising results [21] .…”
Section: Discussionmentioning
confidence: 99%
“…This is for example the case with Diabetes mellitus, where the higher occurrence of sensorineural hearing loss with Diabetes type 1 and 2 is well documented, but the exact neuropathic mechanism is still under debate [33]. Furthermore, in cardiovascular dis-eases, the risk of developing a hearing loss and associated conditions like tinnitus is enhanced but the exact relationship has only been addressed by a few studies [34].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, well-known HI risk factors in the general population include age [ 9 ], genetics, behavioural factors (e.g., smoking and exercise) [ 10 ], environmental exposures (e.g., noise exposure), health care utilization factors (e.g., immunization and antibiotics), and chronic disorders (e.g., hypertension and diabetes) [ 11 ]. Furthermore, various biomarkers involved in inflammation (such as increased white blood cell (WBC) counts, neutrophil (NE) counts, monocyte (MO) counts, and lymphocyte (LY) counts) and metabolic parameters (such as low-density lipoprotein (LDL) and high-density lipoprotein (HDL)) are also recognized as risk indicators of HI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%